2022
DOI: 10.48550/arxiv.2202.09177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Space4HGNN: A Novel, Modularized and Reproducible Platform to Evaluate Heterogeneous Graph Neural Network

Tianyu Zhao,
Cheng Yang,
Yibo Li
et al.

Abstract: Heterogeneous Graph Neural Network (HGNN) has been successfully employed in various tasks, but we cannot accurately know the importance of different design dimensions of HGNNs due to diverse architectures and applied scenarios. Besides, in the research community of HGNNs, implementing and evaluating various tasks still need much human effort. To mitigate these issues, we first propose a unified framework covering most HGNNs, consisting of three components: heterogeneous linear transformation, heterogeneous gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Meta-path plays an essential role in the existing heterogeneous GNNs. However, recent researchers [17] experimentally found that homogeneous GNNs such as GAT [18] actually perform pretty well on heterogeneous graph by revisiting the model design, data preprocessing, and experimental settings of the heterogeneous GNNs, which calls into question the necessity of meta-paths [17], [19]. To answer this question, we first give an in-depth analysis about the intrinsic difference about meta-path-based models (e.g., HAN, MAGNN, GTN) and meta-path-free models (e.g., RGCN [20], GAT, Simple-HGN [17]).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-path plays an essential role in the existing heterogeneous GNNs. However, recent researchers [17] experimentally found that homogeneous GNNs such as GAT [18] actually perform pretty well on heterogeneous graph by revisiting the model design, data preprocessing, and experimental settings of the heterogeneous GNNs, which calls into question the necessity of meta-paths [17], [19]. To answer this question, we first give an in-depth analysis about the intrinsic difference about meta-path-based models (e.g., HAN, MAGNN, GTN) and meta-path-free models (e.g., RGCN [20], GAT, Simple-HGN [17]).…”
Section: Introductionmentioning
confidence: 99%